Synthesis of 2,4-Dinitrophenylhydrazone Derivatives of Co(II), Cu(II) and Ni(II) Complexes of β-Diketones/ β-Ketoesters and Their Antimicrobial Activities. - RAMAN, N.; RAVICHANDRAN, S.; KULANDAISAMY., A. (Asian Journal of Chemistry, 2010)
2,4-Dinitrophenylhydrazone derivatives of Co(ll), Ni(II) and Cu(II) complexes have been synthesized and characterized by elemental analysis, molar conductance, magnetic susceptibility and spectral data. The antimicrobial activities of the complexes have been studied ..